Addendum of Sheikh Muhammad Baha-ud-Din Naqshband in the â€˜Principles of Naqshbandi Sufi Orderâ€™ and its Effectiveness in accomplishing Psychological and Spiritual Advancement - Zulqarnain, Muhammad (http://jagadalimussirry.com/, 2020)
Sufi Orders played a significant role in the religious, moral and spiritual development of people. Particularly, Naqshbandi Sufi Order gained distinguished fame around the globe due to its complete compatibility with Quran and Sunnah and abstain from invented heresies. One of the prominent Sufi Masters of Naqshband â€œSheiek Abdul Khaliq al-Ghujdawaniâ€ introduced eight principles for spiritual enhancement. Shah Baha-ud-Din Naqshband added three more principles which were being recognized â€œPrinciples of Naqshbandi Sufi Orderâ€. This research paper was designed to explore the effectiveness of these three of its eleven basic principles: Temporal pause (ÙˆÙ‚ÙˆÙ Ø²Ù…Ø§Ù†Ù‰), Numerical pause (ÙˆÙ‚ÙˆÙ Ø¹Ø¯Ø¯Ù‰), and Heart pause (ÙˆÙ‚ÙˆÙ Ù‚Ù„Ø¨Ù‰). Qualitative and descriptive research approach was employed in this research for the analysis of data. For clear and better understanding, the article was divided into three sections. The first section gave a brief introduction to famous orders of Sufism, Second explained the Principles of Naqshbandi Sufi order formed by Sheikh Abdul Khaliq Gujdwani, Third looked into addendum of Hazrat Baha-ud-Din in the Naqshbandi principles and explored its effectiveness in psychological and spiritual advancement. The systematic review of literature concluded that these principles played a significant role in psychological, ethical and spiritual enhancement. On one hand they made a strong link between man and Allah in terms of Tawheed, love, and unshakeable trust while on the other hand, provided an opportunity of self-purification from wrong emotions, desires and sinful inclination which ultimately led towards good morals as well as promotion of social peace. It is therefore suggested that religious scholars in general, and Masters of Naqshbandi Sufi order should strictly advise their followers to follow these principles in order to get psychological and spiritual benefits.